The criteria for assessing the opinion of a court expert - Leszczyński, Grzegorz (Prawo Kanoniczne, 2020)
The opinion of a court expert is not final and it does not decide on the invalidity of a marriage concluded by a given subject, as it is up to the judge to assess it and determine its probative value. The function of an expert is only to identify a disease or disorder, to determine its stage at the time of entering marriage by a given subject and to determine its impact on the subject's cognitive and volitional abilities in the context of expressing his consent to the marriage. The judge's task is to evaluate the evidence, including the opinion presented by an expert, and, importantly, to juxtapose it with other circumstances of the case.